2020
DOI: 10.1080/08856257.2020.1776983
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of preparing teachers for inclusive education: case-study of a university in Sweden

Abstract: Sweden is internationally regarded as an inclusive educational system. This study explores how teacher education programmes in Sweden have been organised as regards inclusive education (IE). Specifically, the study examines how teacher candidates and staff perceive teacher pre-service training for IE in terms of its curriculum and pedagogical practices towards students. The question was explored through a case-study of a large, well-respected university in Sweden, using semi-structured interviews and group-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Similarly, a study by Gathumbi et al (2015) reported that lack of teacher training in inclusive education results in teachers being unprepared to manage students with special needs in education. Miskolci et al (2020) state that socio-political factors influence the teachers' understanding about inclusive education, even after their training in special education and inclusion. Although socio-political factors can influence the teachers' preparedness for inclusive education, special education training programs are vital to prepare teachers for inclusive education.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study by Gathumbi et al (2015) reported that lack of teacher training in inclusive education results in teachers being unprepared to manage students with special needs in education. Miskolci et al (2020) state that socio-political factors influence the teachers' understanding about inclusive education, even after their training in special education and inclusion. Although socio-political factors can influence the teachers' preparedness for inclusive education, special education training programs are vital to prepare teachers for inclusive education.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, individual and focused courses on inclusive education need to be strengthened, and all subject specific as well as methodology/didactics lecturers will need to learn about the principles and practices of inclusive education, and be willing to infuse these into their content and assessment. A blend of both these approaches seems the most workable approach (Miškolci et al, 2021).…”
Section: Teacher Education For Inclusionmentioning
confidence: 99%
“…Thus, inclusive education will often be a subject in a course or lectures on special education, rather than within for instance courses or lectures on teaching or the organization of schooling. This has not been a matter of much research in the Swedish context, but a recent study (Miškolci et al, 2020) made a case study of a Swedish university. Key-actors among both teaching and administrative staff, and students from all teacher-training programs-preschool, primary school and upper-secondary school-were interviewed.…”
Section: Inclusion In Swedish Teacher-trainingmentioning
confidence: 99%
“…Rather than challenging this hierarchy, the studied university had developed and incorporated special education courses in their teacher-training programs. As teacher-training is a space in which the future school is hierarchized and shaped, this acceptance of political influence over course-structure and syllabi is revealing as regards the de-prioritization of inclusive education and the tension among these contradictory educational policies risks constraining the university's capacity to prepare its teacher candidates to develop inclusive practices (Miškolci et al, 2020).…”
Section: Inclusion In Swedish Teacher-trainingmentioning
confidence: 99%